Komponen dan Model Pengembangan Kurikulum Pendidikan Agama Islam - Wahyudi, Didi; Srihartini, Yusi; Said, Arjun; Aulia , Frida (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Curriculum as an educational design has a very strategic position in all aspects of educational activities. Given the importance of curriculum development in education, preparation should refer to a strong and strong foundation. The foundation of curriculum development is not only needed by the compiler of the curriculum (macro) or written curriculum which is often referred to as the ideal curriculum, but must also be understood and used as a basis for consideration by the (micro) curriculum implementers, namely education supervisors and teachers and other parties related to the task of education management, as material that will be used as an instrument in coaching the implementation of the curriculum in each type and education level. With this important position, curriculum development cannot be carried out arbitrarily, but must be based on various considerations, or foundations so that it can be used as a foothold in organizing the educational process, thereby facilitating the achievement of educational and learning goals more efficiently and effectively.